Shotguns and stagecoaches the brave men who rode for Wells Fargo in the wild west - Boessenecker, John, 1953- (Farmington Hills, Mich Thorndike Press, a part of Gale, a Cengage Company, 2018)
"The phrase "riding shotgun" was no game to the men who guarded Wells Fargo stagecoaches and trains in the Western frontier. Armed with sawed-off, double-barreled shotguns and an occasional revolver, these men guarded valuable cargo through lawless terrain--battling colorful thieves, vicious highwaymen, and robbers armed with explosives. Wells Fargo always had courageous men to protect its treasure, and their bravery and ingenuity make this book a thrilling read."--
Part one: The Gold Rush era. Well Fargo's pioneer messenger: Pilsbury "Chips" Hodgkins -- The first Wells Fargo detective: Henry Johnson -- From first stage driver to shotgun messenger: Henry C. Ward -- Twelve-gauge justice: Daniel C. Gay -- Part two: The stage robbery era. From Pony Express to Wells Fargo: "Shotgun Jimmy" Brown -- The rifleman: Steve Venard -- A shotgun messenger in old Montana: John X. Beidler -- "Honest, faithful & Brave": Eugene Blair -- Chief Special Officer: James B. Hume -- Riverman, expressman: Andy Hall -- The man who captured Black Bart: Harry N. Morse -- True grit: Mike Tovey -- Vigilante vengeance: Buck Montgomery -- Double-barreled death: Billy Hendricks -- Part three: The train robbery era. "I ain't afraid of any man": Aaron Y. Ross -- Train robbers' nemesis: John N. Thacker -- "Die, damn you!": J. Ernest Smith -- Shotguns and dynamite: Charles F. Charles -- "Send a coffin and a doctor": Jeff Milton -- Fighting wages: David Trousdale -- Epilogue: A legacy squandered.
Unabridged.
Includes bibliographical references (pages 555-618).
108874
Keywords: Wells, Fargo & Company -- Employees -- Biography; 1800-1899; Stagecoaches -- West (U.S.) -- History; Coaching (Transportation) -- West (U.S.) -- History; Stagecoach robberies -- West (U.S.) -- History -- 19th century; Employees; West (U.S.) -- Biography; stagecoach drivers; stage riders; riding shotgun; Large type books; Biographies; History